Detection of increased relative expression units of Bacteroides and Prevotella, and decreased clostridium leptum in stool samples from Brazilian rheumatoid arthritis patients: A pilot study - Rodrigues, Guilherme S. P.; Cayres, Leonardo C. F.; Gonçalves, Fernanda P.; Takaoka, Nauyta N. C.; Lengert, André H.; Tansini, Aline; Brisotti, João L.; Sasdelli, Carolina B. G.; de Oliveira, Gislane L. V. [UNESP] (MDPI, 2019)
Interactions between gut microbes and disease modifying antirheumatic drugs (DMARDs) have been proposed. The aim of the present study was to evaluate the presence of some specific bacteria in stool samples from Brazilian RA patients receiving DMARDs and correlate these data with diet, clinical parameters, and cytokines. Stool samples were used for gut bacteria evalutation by qPCR. Serum samples were used to quantify IL-4 and IL-10 by flow cytometer. Statistics were performed by Pearson chi-square, Mann–Whitney U test, and Spearman’s correlation. The study included 20 RA patients and 30 healthy controls. There were no significant differences (p > 0.05) in dietary habits between RA patients and controls. Concerning gut bacteria, we observed an increase in relative expression units (REU) of Bacteroides and Prevotella species in stool samples from patients, and a decrease in REU of Clostridium leptum when compared with healthy controls. Positive correlation between Prevotella and rheumatoid factor was detected. The IL-4 and IL-10 concentrations were increased in patients when compared with controls. We concluded that gut bacteria are different between RA patients receiving DMARDs and healthy controls. Further studies are necessary to determine the real role of gut microbes and their metabolities in clinical response to different DMARDs in RA patients.
Keywords: Cytokines; Diet; Disease modifying antirheumatic drugs; Gut bacteria; Rheumatoid arthritis